2021
DOI: 10.17269/s41997-020-00453-9
|View full text |Cite
|
Sign up to set email alerts
|

Examining how changes in provincial policy on vape marketing impacted the distribution of vaping advertisements near secondary schools in London, Ontario

Abstract: Objectives On January 1, 2020, the Government of Ontario passed a regulation banning vaping advertisements by retailers, apart from specialty shops. A motivation for this ban was to limit youth exposure to vaping advertisements. The primary goal of this research was to evaluate the impact of this ban on the number and density of vaping advertisements surrounding secondary schools. Additionally, we examined whether the number of vaping advertisements varied by school socio-demographic characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Four studies [76][77][78][79] assessed the impact of ENP advertising restrictions. After Ontario banned vape advertising by retailers, Martin et al [77] observed a 78.2% reduction of vape advertisements within 800 m of secondary schools.…”
Section: Commercial Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Four studies [76][77][78][79] assessed the impact of ENP advertising restrictions. After Ontario banned vape advertising by retailers, Martin et al [77] observed a 78.2% reduction of vape advertisements within 800 m of secondary schools.…”
Section: Commercial Activitymentioning
confidence: 99%
“…Four studies [76][77][78][79] assessed the impact of ENP advertising restrictions. After Ontario banned vape advertising by retailers, Martin et al [77] observed a 78.2% reduction of vape advertisements within 800 m of secondary schools. After Poland banned all advertising, promotion and sponsorships in 2016 [78], one prepost study showed that the presence of any ENP advertising at point-of-sale significantly decreased from 92.0% in 2014 to 30.0% in 2019.…”
Section: Commercial Activitymentioning
confidence: 99%
“…For example, although e-cigarettes have been commercially available in the U.S. for over a decade, it was not until May 2018 that Canada approved nicotine-containing e-cigarettes for sale or promotion. 18 As well, from 2017 to 2019, past month vape use in teenagers increased more rapidly in Canada and the U.S. than it did in Europe, and the increase in exposure to vape advertisements in retail environments since 2018 in Canada likely contributed to this increase. 19 Most recently, as of January 1, 2020, the Government of Ontario banned vape advertising by retailers (apart from vape and cannabis specialty shops) in attempt to reduce youth exposure to vape advertising.…”
Section: Introductionmentioning
confidence: 99%
“…New evidence suggests that this ban has substantially reduced vaping promotions, as well as socio-demographic inequalities in youth exposure to marketing of vape products. 18 …”
Section: Introductionmentioning
confidence: 99%